Groundswell : Women of Land Art - Arnold, Leigh A.; Hutchinson, Scout; La Brasca, Jana; Lovatt, Anna; Sorkin, Jenni; Thompson, Anne (Dallas, Texas ; New York : Nasher Sculpture Center : Del Monico Books D.A.P., 2023)
Albuquerque, Lita ; Aycock, Alice ; Buchanan, Beverly ; Denes, Agnes ; Hassinger, Maren ; Holt, Nancy ; Johanson, Patricia ; Mendieta, Ana ; Miss, Mary ; Pinto, Jody ; Stuart, Michelle ; Webster, Meg
Groundswell: Women of Land Art, Nasher Sculpture Center, Dallas, September 23, 2023 - January 7, 2024
boek